Bundled Defect‐Rich MoS2 for a High‐Rate and Long‐Life Sodium‐Ion Battery: Achieving 3D Diffusion of Sodium Ion by Vacancies to Improve Kinetics. Issue 12 (20th February 2019) - Yao, Kai; Xu, Zhanwei; Huang, Jianfeng; Ma, Meng; Fu, Licai; Shen, Xuetao; Li, Jia; Fu, Maosen
Abstract: Molybdenum disulfide (MoS2 ), a 2D‐layered compound, is regarded as a promising anode for sodium‐ion batteries (SIBs) due to its attractive theoretical capacity and low cost. The main challenges associated with MoS2 are the low rate capability suffering from the sluggish kinetics of Na + intercalation and the poor cycling stability owning to the stack of MoS2 sheets. In this work, a unique architecture of bundled defect‐rich MoS2 (BD‐MoS2 ) that consists of MoS2 with large vacancies bundled by ultrathin MoO3 is achieved via a facile quenching process. When employed as anode for a SIB, the BD‐MoS2 electrode exhibits an ultrafast charge/discharge due to the pseudocapacitive‐controlled Na + storage mechanism in it. Further experimental and theoretical calculations show that Na + is able to cross the MoS2 layer by vacancies, not only limited to diffusion along the layer, thus realizing a 3D Na + diffusion with faster kinetics. Meanwhile, the bundling architecture reduces the stack of sheets with a superior cycle life illustrating the highly reversible capacities of 350 and 272 mAh g −1 at 2 and 5 A g −1 after 1000 cycles. Abstract : Bundled defect‐rich MoS2 is achieved by quenching MoS2 sheet. Na + can cross MoS2 layers by vacancies and is not limited to diffusion along the layer, realizing 3D diffusion for high rate capability. The bundled architecture reduces the stack of sheets with a superior cycle life, illustrating the capacities of 350 and 272 mAh g −1 at 2 and 5 A g −1 after 1000 cycles.